Governance sebagai Pengelolaan Konflik - Arfani, Riza Noer (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2005)
The article explores the notion of understanding governance as part of conflict management, or vice versa, of undustanding conflict management aspects as benefiting from governance concepts and practices. Governance, with its much broader meaning than government, suggests diverse relevant and significant clues, hints and ideas in the context of conflict management endeavors. one of which is the idea to involve larger audiences and stakeholders âbeyond the conventional institutions such as governmental bodiesâ in policy making processes and public discourses. Such comprehension and appreciation of governance concepts and practices is certainly parallel with the conflict management philosophies, concepis and practices which based on and oriented toward integrative, non-formal and non-litigative mechanisms.